2022
DOI: 10.1021/acsabm.1c01153
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical DNA Biosensors Based on the Intrinsic Topological Insulator BiSbTeSe2 for Potential Application in HIV Determination

Abstract: In this work, we reported a sensitive, label-free electrochemical biosensor based on the intrinsic topological insulator (TI) BiSbTeSe2 for potential application in the determination of the HIV gene. With strong spin–obit coupling, TIs could have robust surface states with low electronic noise, which might be beneficial for the stable and sensitive electron transport between the electrode and electrolyte interface. Under optimized conditions of the biosensors using BiSbTeSe2, the differential pulse voltammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…As a novel quaternary TI material, the BiSbTeSe2 has obtained some interesting results in recent years due to its strong spin-orbit coupling effect and stable energy gap. [45][46][47] Some studies have shown that the band gap of the BiSbTeSe2 is 0.25 eV, [48] and the carrier density can reach 10 12 cm −2 . [49] At the same time, German et al have shown that the BiSbTeSe2 is one of the most bulkinsulating three-dimensional TIs, [50] which makes it important in the TI research.…”
mentioning
confidence: 99%
“…As a novel quaternary TI material, the BiSbTeSe2 has obtained some interesting results in recent years due to its strong spin-orbit coupling effect and stable energy gap. [45][46][47] Some studies have shown that the band gap of the BiSbTeSe2 is 0.25 eV, [48] and the carrier density can reach 10 12 cm −2 . [49] At the same time, German et al have shown that the BiSbTeSe2 is one of the most bulkinsulating three-dimensional TIs, [50] which makes it important in the TI research.…”
mentioning
confidence: 99%
“…This research was of great significance for the reliability and security of power systems and provided valuable research and application references for related fields [ 15 ]. Jiang et al (2022) opted for optimized texture features to project insulator images and searched for insulator position information through the projected images [ 16 ]. Liu et al (2021) applied the Harris corner detection algorithm to both the target image and the template image, matching feature information with template feature information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is an electrochemical biosensor, where the peak of the DPV current varies for single-stranded DNA (ssDNA) and dsDNA. Using the intrinsic topological insulator (TI) BiSbTeSe 2 , Jiang et al [40], have developed a very sensitive, label-free electrochemical biosensor that can be used to determine HIV gene expression. In addition to having stable and sensitive electron transport, TIs with strong spin-orbit coupling may have robust surface states with low electronic noise.…”
Section: Graphene-based Biosensorsmentioning
confidence: 99%
“…DPV peak currents performed well after storage at 4°C for 7 days, and the biosensors had good selectivity and stability. Using topological materials, this study provides an effective method of developing biosensors that can be used for the determination of clinical markers and monitoring [40]. In another similar study by Xiong et al [41], a large-size Bi 2 Se 3 tape electrode (BTE) was prepared using a single crystal of 2 cm × 1 cm × 0.5 cm.…”
Section: Graphene-based Biosensorsmentioning
confidence: 99%